Borealpox Virus: a Comprehensive Review of its Emergence and Global Recommendations - Omoruyi, Pius Omosigho; Okesanya, Olalekan John; Amisu, Blessing Olawunmi; Ukoaka, Bonaventure Michael; Manirambona, Emery; Okon, Inihebe Ime; Jamil, Safayet; Ogaya, Jerico Bautista; Ndukwe, Rachael Ogadinma; Ogieuhi, Ikponmwosa Jude; Lucero-Prisno III, Don Eliseo (Journal of Health Science and Medical Research, 2025)
The emergence of the Borealpox virus (BRPV), formerly known as the Alaskapox virus (AKPV), in 2015 poses an intriguing scientific challenge. Despite being first discovered in Alaska, BRPV is a potential global threat, and reports of instances have raised questions about how serious it can be; especially in those with impaired immune systems. The unique characteristics of BRPV have been clarified through genomic characterization, providing insight into its evolutionary lineage and transmission dynamics. A recent death linked to BRPV highlights the difficulties presented by newly developing infectious illnesses, particularly for individuals who are already at risk. The implications of BRPV for public health call for all-encompassing management approaches; such as creating efficient treatments and customized interventions for various clinical presentations. Research and surveillance initiatives are vital for comprehending ecological reservoirs and patterns of transmission. Additionally, biosafety regulations and immunization programs are critical for controlling outbreaks and reducing the worldwide effects of BRPV. Prioritizing vaccination drive approaches, implementing stringent infection control measures, and reinvigorating disease surveillance systems are imperative for preventing BRPV. In addition, enhancing the training of frontline healthcare professionals and implementing the One Health concept are crucial measures that foster robust cooperation and adaptability, while confronting new public health concerns. A comprehensive review of the emergence and consequences of the Borealpox virus is necessary to direct future investigations and global public health campaigns. By utilizing interdisciplinary approaches and promoting global collaboration, we may successfully alleviate the danger presented by BRPV and protect public health across borders.